Haemodynamic and anatomic progression of aortic stenosis. Issue 12 (5th February 2015) - Nguyen, Virginia; Cimadevilla, Claire; Estellat, Candice; Codogno, Isabelle; Huart, Virginie; Benessiano, Joelle; Duval, Xavier; Pibarot, Philippe; Clavel, Marie Annick; Enriquez-Sarano, Maurice; Vahanian, Alec; Messika-Zeitoun, David
Abstract : Background: Aortic valve stenosis (AS) is a progressive disease, but the impact of baseline AS haemodynamic or anatomic severity on AS progression remains unclear. Methods: In 149 patients (104 mild AS, 36 moderate AS and 9 severe AS) enrolled in 2 ongoing prospective cohorts (COFRASA/GENERAC), we evaluated AS haemodynamic severity at baseline and yearly, thereafter, using echocardiography (mean pressure gradient (MPG)) and AS anatomic severity using CT (degree of aortic valve calcification (AVC)). Results: After a mean follow-up of 2.9±1.0 years, mean MGP increased from 22±11 to 30±16 mm Hg (+3±3 mm Hg/year), and mean AVC from 1108±891 to 1640±1251 AU (arbitrary units) (+188±176 AU/year). Progression of AS was strongly related to baseline haemodynamic severity (+2±3 mm Hg/year in mild AS, +4±3 mm Hg/year in moderate AS and +5±5 mm Hg/year in severe AS (p=0.01)), and baseline haemodynamic severity was an independent predictor of haemodynamic progression (p=0.0003). Annualised haemodynamic and anatomic progression rates were significantly correlated (r=0.55, p<0.0001), but AVC progression rate was also significantly associated with baseline haemodynamic severity (+141±133 AU/year in mild AS, +279±189 AU/year in moderate AS and +361±293 AU/year in severe AS, p<0.0001), and both baseline MPG and baseline AVC were independent determinants of AVC progression (p<0.0001). Conclusions: AS progressed faster with increasing haemodynamic or anatomic severity. Our results suggest that a medical strategy aimed at preventing AVC progression may be useful in all subsets of patients with AS including those with severe AS and support the recommended closer follow-up of patients with AS as AS severity increases. Clinical trial registration: COFRASA (clinicalTrial.gov number NCT 00338676) and GENERAC (clinicalTrial.gov number NCT00647088 ).